Korelasi Keterampilan Membaca Pemahaman dengan Keterampilan Menulis Teks Tanggapan Siswa Kelas VII SMP - Tusyadiyah, Halimah; Amir, Amril; Afnita, Afnita; Anggraini, Dewi (Universitas Muhammadiyah Magelang, 2026)
The purpose of this study is to describe the following things. First, to describe the level of reading comprehension skills of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency. Second, to describe the level of writing response text skills of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency. Third, to describe the level of reading comprehension skills of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency. This type of research is quantitative with a descriptive method with a correlational design. The research design used is a correlational relationship between two variables. The population of this study was seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency registered in the 2025/2026 academic year with a total of 249 students. The sample in this study amounted to 71 students. The research sample was taken using the Slovin formula with a proportional random sampling technique. The research instrument was a test, namely an objective test of reading comprehension skills and a performance test of writing response text skills. There are three research results as follows. First, the reading comprehension skills of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency are in good qualifications with an average value of (76.67). Second, the writing skills of response texts of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency are in good qualifications with an average value of (82.51). Third, a significant correlation between reading comprehension skills and writing skills of response texts of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency at n-1 degrees of freedom (71-1) and a significance level of 95%, the h value (9.213) is greater than t table (1.669). Thus, it can be concluded that there is a significant correlation between reading comprehension skills and writing skills of response texts of seventh grade students of SMP Negeri 3 Batang Anai, Padang Pariaman Regency. Keywords: Correlation, Reading Comprehension Skills, Writing Response Texts